«For the justice of His cause that God defends»: José de San Martín and the republican liturgy - Piccone Camere, Carlos (Mercurio Peruano, 2018)
After Peruvian independence, the "divine factor" seemed to take a very different direction, taking distance from both parties, as an increasing process of ecclesiological Romanization began, insofar as a political theology was being put into practice according to the guidelines issued from Rome. Thus, although in the history of South American independence there is a constant invocation of God’s name to defend "the justice of the cause" of a determined political and social system, thanks to the abundance of available sources from one and the other perspective , the Peruvian case is, in historiographical terms, one of the most complex and disturbing.